2007
DOI: 10.1007/s10659-007-9111-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Active Response of Soft Living Tissues

Abstract: Soft tissues exhibit a nonlinear, essentially incompressible (visco-) elastic response; a key issue is the active nature of muscle fibres, in other words their ability to contract and relax in response to biochemical signals. Here we present a continuum model able to describe an active elastic medium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 23 publications
0
99
0
Order By: Relevance
“…The elastic deformations result from the multiplicative decomposition once the compatibility of the global bending deformation has been ensured; they deliver internal stresses within the gel beam corresponding, in the absence of external forces, to null forces and torques on each cross section of the beam. Importantly, we note that both the components of the deformation have an elastic nature, which is different from what happens when a similar multiplicative decomposition is used to describe growth or thermal processes [8][9][10]; hence, both the components of the multiplicative decomposition depend on the elastic properties of the gel. We have shown that our simple bending model predicts material responsiveness in excellent agreement with the outcomes of our pilot study.…”
Section: Introductionmentioning
confidence: 81%
“…The elastic deformations result from the multiplicative decomposition once the compatibility of the global bending deformation has been ensured; they deliver internal stresses within the gel beam corresponding, in the absence of external forces, to null forces and torques on each cross section of the beam. Importantly, we note that both the components of the deformation have an elastic nature, which is different from what happens when a similar multiplicative decomposition is used to describe growth or thermal processes [8][9][10]; hence, both the components of the multiplicative decomposition depend on the elastic properties of the gel. We have shown that our simple bending model predicts material responsiveness in excellent agreement with the outcomes of our pilot study.…”
Section: Introductionmentioning
confidence: 81%
“…Such a decomposition accounts for introducing an intermediate frame between the reference and the deformed configurations. The microscopic part of the deformation gradient takes the form [27] …”
Section: Dislocation Approachmentioning
confidence: 99%
“…The upscaling strategy is incorporated in the model following an anisotropic active strain formalism [27,41], where the force balance determining the motion of the tissue depends on local distortion of the microstructure followed by a macroscopic rearrangement of the material recovering compatibility of the deformation. Mathematically, this corresponds to a decomposition of strains.…”
Section: Introductionmentioning
confidence: 99%
“…In order to account for the activation of the cardiac contraction, we follow a model of active strain (Nardinocchi & Teresi, 2007;Cherubini et al, 2009;Rossi et al, 2012), where we assume a multiplicative decomposition of the deformation gradient into a passive and an active component, F = F E F A . This assumption means that the energy is not stored as strain energy, rather it corresponds to an internal rearrangement of the material that does not produce macroscopic deformation.…”
Section: Kinematicsmentioning
confidence: 99%